Saysay himig a sourcebook on Philippine music history, 1880-1941 - Tan, Arwin Q.; Tan, Arwin Q. (Music and culture book series, 2018)
The chapters are organized around six general themes. These include (1) transmission of music, (2) musical heritage, (3) politics and music, (4) music economy, (5) popular culture, and (6) music communities. Individual topics include but are not limited to audience reception of and writing about music in Manila in various decades; overviews of particular genres or styles— including folk music traditions, rondalla, zarzuela (sarsuwela), bodabil, and opera—in the Philippines; music pedagogy in the Philippines; systems for printing, publishing, selling, and copyrighting music in Manila; and the intersections of US imperialism with music education and performance--Project Muse, Asian Music Volume 53, Number 2, Summer/Fall 2022, pp. 140 (Review)